The British Services Dhaulagiri Medical Research Expedition 2016: a unique military and civilian research collaboration. Issue 6 (5th October 2017) - Mellor, Adrian; Bakker-Dyos, J; Howard, M; Boos, C; Cooke, M; Vincent, E; Scott, P; O'Hara, J; Clarke, S B; Barlow, M; Matu, J; Deighton, K; et al.
Abstract : Introduction: High-altitude environments lead to a significant physiological challenge and disease processes which can be life threatening; operational effectiveness at high altitude can be severely compromised. The UK military research is investigating ways of mitigating the physiological effects of high altitude. Methods: The British Service Dhaulagiri Research Expedition took place from March to May 2016, and the military personnel were invited to consent to a variety of study protocols investigating adaptation to high altitudes and diagnosis of high-altitude illness. The studies took place in remote and austere environments at altitudes of up to 7500 m. Results: This paper gives an overview of the individual research protocols investigated, the execution of the expedition and the challenges involved. 129 servicemen and women were involved at altitudes of up to 7500 m; 8 research protocols were investigated. Conclusions: The outputs from these studies will help to individualise the acclimatisation process and inform strategies for pre-acclimatisation should troops ever need to deploy at high altitude at short notice.